2000
DOI: 10.1081/clt-100100931
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Transient Diabetes Insipidus Associated with Poisoning by a Herbicide Containing Glufosinate

Abstract: A 60-year-old man ingested 500 mL of BASTA herbicide in a suicide attempt. He developed not only unconsciousness, respiratory distress, and convulsions but also an increase in urine output (7885 mL/d), elevated serum sodium (167 mEq/L), elevated plasma osmolality (332 mOsm/kg), and a decrease in both urine osmolality (200 mOsm/kg) and urine specific gravity (1.003), which suggested the development of diabetes insipidus. The plasma level of antidiuretic hormone remained within the normal range (1.3 pg/mL), desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…19 Recovery from glufosinate poisoning is prolonged and extubation may be delayed for a week or more. Central diabetes insipidus has been well documented in one reported case 20 but was not present in our patient.…”
Section: Discussioncontrasting
confidence: 48%
“…19 Recovery from glufosinate poisoning is prolonged and extubation may be delayed for a week or more. Central diabetes insipidus has been well documented in one reported case 20 but was not present in our patient.…”
Section: Discussioncontrasting
confidence: 48%
“…Several case studies of diabetes induced by pesticide poisoning have been reported (Takahashi et al 2000), and one study of 23 subjects admitted to an Indian intensive care unit with carbamate or organophosphate poisoning found 69% of subjects demonstrated transient glycosuria (Shobha and Prakash 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had central DI as the patient responded after desmopressin. There have been a few case reports of central DI following malathion [5], glufosinate [6], carbon monoxide [7] poisoning and overdose of baclofen and quetiapine [8] but there has been no case report following diethyl compound of OP. Central DI is common following pituitary surgery, tumour, infections, granulomas, inflammatory condition, vascular, chemical toxin and genetic but 50% is idiopathic [9], and our patient did not any of these causes.…”
Section: Discussionmentioning
confidence: 99%